Speech Disfluencies of Non-Native Speakers of English in TED Talk Scripts - Veronica Esti Nugrahani; Barli Bram (Institut Agama Islam Negeri Palopo, 2022)
To speak fluently in the target language, English, has remained a challenge for learners, particularly those who are non-native speakers of English. When speaking, therefore, learners should be aware of speech disfluencies. This paper, accordingly, investigates the speech disfluencies of non-native speakers in their presentations. Data were collected from TED Talk scripts and were then analysed and discussed, based on categories of disfluency. The findings of this document analysis reveal five types of disfluency in the data, namely unfilled pause, filled pause, repetition, deletion, and substitution. It is expected that learners of English at university level can benefit from the study results concerning speech disfluencies to improve their speaking proficiency. Keywords: Disfluency; filled pause; non-native speaker; TED talk